Perbandingan Prediksi Financial Distress Menggunakan Model Altman, Grover dan Zmijewski - Gunawan, Barbara; Pamungkas, Rahadien; Susilawati, Desi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This research aims to find predictors model of Financial Distress which are the most accurate in predicting the condition of Financial Distress at manufacturing companies. The populations/objects in this research are all of the manufacturing companies that listed on the Indonesia Stock Exchange (known as BEI) in 2014. In this research, the technique of sampling used is Purposive Sampling. The sample of this research totaled 110 manufacturing company. Total data in the research is 110 annual reports. Methods of analysis used were multiple linear regressions using SPSS program 15.00.The results showed that the Model Model Altman, Grover, and Model Zmijewski can be used to predict the condition of Financial Distress. Between these three models, model Zmijewski is the most accurate model to predict the condition of Financial Distress at manufacturing companies.